(untitled) (Altre Modernità, 2025)
“On 8M [2018] in Madrid they did try to be with the Asociación Gitanas Feministas por la Diversidad, but in the end the manifesto they read did not include our protests. We can’t go on a general strike because we don’t have jobs to go on strike”. The words of Silvia Agüero, a gypsy feminist who recovers the memory of the oppression of the gypsy community, revealed a flaw in the powerful feminist demonstration of 8 March 2018 and that continues to exist in white hegemonic feminism and with class and racial privilege, making us lose sight of the common problem of a capitalist system that hand in hand with patriarchy continues to dehumanise and keep all feminised subjects subjugated. Many of the members of the Asociación Gitanas Feministas por la Diversidad ask themselves if 8M belongs to them, if its history and genesis are not alien to the history of the Roma community, if they feel recognised in a demonstration that has its roots in Working Women’s Day. Exploring the feminist movement of recent years, the aim of this article is to observe how Antigypsyism in Spain is currently confronted by Romani women by analysing the main issues and strategies that emerge around the articulation between the feminist struggle and the struggle against Antigypsyism. From the theoretical perspective of intersectional feminism, the purpose of this work is to reveal the main themes around which Roma feminism builds its struggles and the different strategies—including artistic ones—that it employs to confront ’payo’ feminism with its racial prejudices: pedagogy, denunciation, the call to action and the construction of networks and alliances.